Do blood contamination and haemostatic agents affect microtensile bond strength of dual cured resin cement to dentin? - Kerem KiLiC; Soley ARSLAN; Goknil Alkan DEMETOGLU; Gokmen ZARARSIZ; Bulent KESiM (University of São Paulo, 2013)
Objective The purpose of this study was to evaluate the effects of blood contamination and haemostatic agents such as Ankaferd Blood Stopper (ABS) and hydrogen peroxide (H2O2) on the microtensile bond strength between dual cured resin cement-dentin interface. Material and Methods Twelve pressed lithium disilicate glass ceramics were luted to flat occlusal dentin surfaces with Panavia F under the following conditions: Control Group: no contamination, Group Blood: blood contamination, Group ABS: ABS contamination Group H2O2: H2O2 contamination. The specimens were sectioned to the beams and microtensile testing was carried out. Failure modes were classified under stereomicroscope. Two specimens were randomly selected from each group, and SEM analyses were performed. Results There were significant differences in microtensile bond strengths (µTBS) between the control and blood-contaminated groups (p<0.05), whereas there were no significant differences found between the control and the other groups (p>0.05). Conclusions Contamination by blood of dentin surface prior to bonding reduced the bond strength between resin cement and the dentin. Ankaferd Blood Stoper and H2O2 could be used safely as blood stopping agents during cementation of all-ceramics to dentin to prevent bond failure due to blood contamination.